Orang Tua sebagai Tenaga Pendidik - Mohammad Rachmad Ibrahim (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: The progress of education runs relevantly by parental partnership. Good environmental of home, school and college build students' character according to the goal of education itsetl. Today's demand is normalization of education as 'a must' Infrastructures and cuniculum would not be significant if any educators who are loyal to the quality of education are still rare. Moral education as the intangible product which is needed as power of character buitding in every place shoutd be enriched by parents who conscious about their future, ofkpring, famity, religion, nation and even internationally. All educators should concern about students intelligences (multipleintelligences, learning styte, learning acceptance) and direct (self-efficacy and self-motivation) them in achievement of their goal in the future.